On Neoclassical Models of Economic Growth - Inada, Ken-Ichi (Review of Economic Studies, 1965)
Journal Article On Neoclassical Models of Economic Growth Get access Ken-ichi Inada Ken-ichi Inada Tokyo Metropolitan University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 32, Issue 2, April 1965, Pages 151–160, https://doi.org/10.2307/2296059 Published: 01 April 1965